2007
DOI: 10.1038/sj.ijo.0803605
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in adiposity in toddlers and preschoolers in the GENESIS study and associations with the ACE I/D polymorphism

Abstract: Objectives: To investigate the relationship between the angiotensin I-converting enzyme 1 (ACE) I/D polymorphism and adiposity-related phenotypes in a large cohort of toddlers and preschoolers. Methods: Body composition measurements and DNA samples were obtained from 2102 Greek children aged 1-6 years, as part of a large-scale epidemiological study (GENESIS). All children were genotyped for the ACE I/D polymorphism and gender-and age-stratified statistical analyses were performed. Results: In girls aged 4-6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
(47 reference statements)
2
21
1
1
Order By: Relevance
“…Similarly, these polymorphisms were not associated with indexes of obesity in the Chinese population [60], Korean [61] and Iranian females [62] or Romanian T2DM patients [63]. In contrast with these data, the ACE ID variants [64][65][66] and the AT1R CC genotype [67] were associated with markers of obesity in other studies.…”
Section: Discussioncontrasting
confidence: 47%
“…Similarly, these polymorphisms were not associated with indexes of obesity in the Chinese population [60], Korean [61] and Iranian females [62] or Romanian T2DM patients [63]. In contrast with these data, the ACE ID variants [64][65][66] and the AT1R CC genotype [67] were associated with markers of obesity in other studies.…”
Section: Discussioncontrasting
confidence: 47%
“…Studies in the Czech Republic [6] showed that I/D polymorphisms of ACE gene were correlated with obesity [15][16][17]30] in children and adults as well. They explained that 47 % of the plasma variation of ACE activity is due to a polymorphism located in intron 16 of the ACE gene, and the increased ACE activity is associated with D allele [31].…”
Section: Discussionmentioning
confidence: 98%
“…Based on the previously mentioned studies [10,[15][16][17], we investigated the role of ACE gene polymorphisms (I/D) in obese or malnourished children by comparing mentioned polymorphisms with anthropometric measurements (BMI-body mass index, MUAC-middle upper arm circumference and TST-tricipital skinfold thickness) and some laboratory analysis, as well as establishing correlations between the two groups and the control group. From the laboratory parameters, we have chosen protein and albumin levels because they better characterize the nutritional state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The common insertion/deletion polymorphism (ID ACE; rs 4646994) in the gene for angiotensin-converting enzyme (ACE) was previously associated with obesity [3,15,19,30], both in preschoolers, adolescents and adults. Previously, it has been also reported that approximately 47% of the variance in plasma ACE activity can be explained by this polymorphism located in intron 16 of the ACE gene, the D allele being associated with increased ACE activity [25].…”
Section: Introductionmentioning
confidence: 99%